A perspective on systems thinking, architecting, and art. (2nd September 2019) - McDermott, Tom; Salado, Alejandro
Abstract: Systems architecture has been considered as both an art and a science. The systems architect uses heuristics, stories, and models to communicate complex architectural concepts to stakeholders. Since the earliest times, master building architects have developed their skills broadly across the technical, business, and fine art domains. Why should engineering be different? Principles and practices of systems architecture are exhibited in the creation of film scores, fine arts, and building architecture. Why not teach art as a core skill of the systems architect? In this work, we explore a formal competency model linking art, systems thinking, and systems architecture. We associate competencies across these domains with the concept of elegant design. We explore formal education in the arts as a way to bridge the communication problems that technical architects have with their stakeholders. The goal is to improve the competencies of systems architects and systems thinkers by bringing the methods of the art studio class to systems education.